Pengaruh Faktor Sosial Demografi Dan Ekonomi Terhadap Keputusan Ingin Atau Tidak Menetap Pelaku Mobilitas Di Kota Denpasar - Agustina, Putu Wira; Yasa, I.G.W Murjana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 10, Oktober 2013 (pp. 434-491), 2013)
This studyaimed to determine the effect of age , marital status, education level, number of dependents and income of the decision to settle or not settle like actors circular mobility. The research was conducted in two urban villages in the city of Denpasar that is Village Pemecutan West Denpasar Districtand Village Pemogan South Denpasar District. Number ofsamples taken is 95 non-permanent migrants, with purposive sampling method. Data was collected through structured interviews , whereas analytical techniques used are binary logistic regression. Based onthe results of a partial analysis of the independent variables, agehad no significant effect while the variable marital status, education level, number of dependen s and income significantly influence the decision of actors want to settle circular mobility. A total of 56 of  the 95respondens chose not to settle, while 39 respondents chose to settle in the goal area.
Keywords: Mobilitycircular , binary logisticregression , settledornotsettle